Determination of baseline data on respirable dust concentration for safety and health enhancement in selected small and medium industries in Johor - Paiman, Nuur Azreen (2014)
Air pollution has become the major global concern regarding to the harmful health effect, increased morbidity, and mortality especially for particulate air pollutant. However, there is still very limited study that discussed the effects of exposures of dust and particle matters in industry at Malaysia especially respirable dust. This study was focus on the respirable dust concentration and their respirable health symptoms in selected industry. Three (3) case studies had been done as data collection. For each case, several sampling location was chosen for sampling station and several workers was randomly choosen as respondents in assessing the exposure of respirable dust by using personal environmental monitoring (PEM) method. Series of a direct reading measurement for area sampling of respirable dust (PM10), carbon dioxide (CO2), temperature and relative humidity were also conducted at the same time. Questionnaires were administrated in purposed to determine the respiratory health problem symptoms and supported by lung function test by using spirometer with a standard method of sampling. The result of the study showed most of the workers in paper based mill were exposed to respirable dust when the Time Weightage Average (TWA) result was above the permissible exposure limit which is 5 mg/m3 and 3 mg/m3 from Occupational Safety and Health Administration (OSHA) and American Conference of Governmental Industrial Hygienists (ACGIH) standard respectively. From the survey feedbacks, out of 30 symptoms, there are only five symptoms that are significant with the year of exposure. For pulmonary lung function test, there were 81.81% (paper based mill), 53.33% (palm oil mill) and 65.63% for automotive plant were in normal spiro status respectively. Significant reduction was observed in the mean values of Force Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), and Force Expiratory Ratio (FEV1/FVC) among workers. It is concluded that lung function among exposure workers is impaired and stratification of result shows a respiratory health symptoms effects of years to respirable dust exposure on lung function.